(3GdeYGedI GdVQjHjI ddTQcGJ GdESJNQGLjI (B: s (3OQGSI ebGQfI (B/ s - (3QeVGf UOjb eMeO MSjfs; (3GdSjO GdSjO YHO Gdehdis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQIs, 1993)
(3gOaJ GdOQGSI Edi EHQGR fhGMi GdJTGHg hGdENJdGa ai GdeYGedI GdVQjHjI GdJi JJYQV dgG GdTQcGJ GdGSJQGJjLjI hZjQgG ef GdeTQhYGJ GdCNQi, hNGUI ai eLGd aQV GdVQjHI Ydi GdONd Ch GdCQHGM, hCSHGH Pdc hGdeTcdGJ GdJi JJQJH YdjgG hEJLGgGJ GdOhd GdeNJdaI dMdgG, heOi JWHjb Pdc Ydi GdfXGe GdVQjHi dgPg GdTQcGJ ai eUQ(B. (3GSJNOe GdefgL GdebGQf hJe GNJjGQ fehPLjf geG(B: (3GdfehPL GdChd hjNJU HOQGSI GdfXe GdVQjHjI dHYV GdOhd GdJi JfJei EdjgG GdTQcGJ GdGSJQGJjLjI hef CgegG GdfXGe GdVQjHi GdCeQjci hGdfXGe GdVQjHi GdHQjWGfi, CeG GdfehPL GdKGfi ajJfGhd OQGSI GdfXe GdVQjHjI GdJi JCNP HgG GdOhd GdeVjaI GdJi JYed ajgG gPg GdTQcGJ, hNGUI GdOhd GdYQHjI(B. (3ChVMJ GdOQGSI edGeM GdeYGedI GdVQjHjI ddTQcGJ GdGSJQGJjLjI hGdMGLI Edi eYGedI VQjHjI NGUI ddfTGW GdGSJQGJjLi, Ke fhbTJ GdfJGFL(B. (3h bSe GdHGMK GdQSGdI Gdi HGH JegjOi (B: (3jJfGhd HGdYQV dUhQ GdaQGFV GdeGdjI GdJi jecf Gf JMUd YdjgG GdOhdI ef GdfTGW GdGSJNQGLi ShGA JMOOJ gPg GdaQGFV Ydi GSGS GdGfJGL Gh HfGA Ydi ebOGQ GdONd Gh GdQHM GdPi JMbbg gPg GdTQcGJ , hNeS GHhGH (B: (3GdGhd (B: (3jMOO fWGb GdVQjHI , GdKGfi (B: (3jhVM UhQ GdGjQGOGJ Gh GdONhd GdJi JNVY ddVQjHI hGSS JMOjOgG , GdKGdK (B: (3jJYQV ddfabGJ GdJi jecf NUegG ef GdONd GdNGVY ddVQjHI hGMcGegG , GdQGHY (B: (3jYQV dbhGYO JMOjO GQHGM GdTQcGJ GdGSJNQGLjI OhdjI GdfTGW hGSS JhRjY GdGQHGM GdNGUI Hcd Ohdg , GdNGeS (B: (3jOhQ Mhd Gge GdMhGaR GdeGdjI GdVQjHjI GdJi jecf Gf JefM Gh JMQe efgG GdTQcGJ GdGSJNQGLjI (B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj (B1993.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B557-568.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVQGFHs; (3GdaQGFV GdeGdjIs; (3GdfabGJ GdYGeIs; (3bhGYO GdJSYjQs; (3GdCQHGMs; (3GdGSJgdGcs; (3GdNUNUIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjY GdVQjHjs